Guidance Note for Developing Government Local Currency Bond Markets - Hashimoto, Hideo; Mooi, Yen; Pedras, Guilherme; Roy, Arindam; Chung, Kay; Galeza, Tadeusz; Papaioannou, Michael G.; Katz, Peter; Bango, Zsolt; Gragnani, Jose Antonio; Gurhy, Bryan; Paladines, Cindy (Washington, DC : World Bank, 2022)
This guidance note was prepared by International Monetary Fund (IMF) and World Bank Group staff under a project undertaken with the support of grants from the Financial Sector Reform and Strengthening Initiative, (FIRST). The aim of the project was to deliver a report that provides emerging market and developing economies with guidance and a roadmap in developing their local currency bond markets (LCBMs). This note will also inform technical assistance missions in advising authorities on the formulation of policies to deepen LCBMs. The guidance note discusses commonly faced challenges and bottlenecks in the journey to efficient and deep LCBMs. In particular, the guidance note explores how to overcome difficulties in implementing some existing best practices. Experience points to the interdependent nature of the required development actions and the need for supportive actions outside the narrow field of LCBM agents. The challenges discussed and accompanying policy guidance draw from the IMF and World Bank’s extensive technical assistance (TA) provision in this area, cross-country experience in LCBM development, and results from a recent survey of country authorities. The guidance note intends to be a resource for a wide range of stakeholders interested in government bond market development. Country authorities and TA providers can use the diagnostic on the level of LCBM development to design a proper sequence of policy actions to further improve the functioning of the domestic government debt market. Country authorities and IMF and World Bank country teams can use the guidance note to identify key macroeconomic and financial issues linked to LCBM development and integrate it into their policy analysis and advice. The diagnostic findings regarding weaknesses in LCBMs also can be used to help identify financial vulnerabilities and their remedies, in the authorities’ ongoing financial sector surveillance and in the context of Financial Sector Assessment Programs and Financial Sector Stability Reviews.